Penguatan Keluarga dalam Pendidikan Anak di Masa Pandemi Covid-19 - Nuraeni Nuraeni; I Made Sonny Gunawan; Suharyani Suharyani (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The purpose of this community service activity is to increase the knowledge and understanding of parents on the importance of understanding emotions in order to care for and teach children to learn at home to be more fun. This community service activity is carried out by providing counseling in the form of socialization and technical guidance for school principals and elementary school teachers throughout Mataram. There were 60 participants in this community service activity. The results of this community service show the active participation of school principals and elementary school teachers, which can be seen from the many questions asked by community service activity participants. In addition, from what has been said, many teachers are interested in wanting to learn again about ways to manage emotions, so the community service team plans to provide training for teachers as a form of follow-up activities.